2023
DOI: 10.3389/fgene.2023.1137017
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms of microRNAs in endocrine disorders and their therapeutic potential

Abstract: MicroRNAs (miRNAs) are small endogenous non-coding RNA molecules capable of regulating gene expression at the post-transcriptional level either by translational inhibition or mRNA degradation and have recently been importantly related to the diagnosis and prognosis of the most relevant endocrine disorders. The endocrine system comprises various highly vascularized ductless organs regulating metabolism, growth and development, and sexual function. Endocrine disorders constitute the fifth principal cause of deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 104 publications
(168 reference statements)
0
10
0
Order By: Relevance
“…Small non-coding RNA molecules called microRNAs (miRNAs) are essential for post-transcriptional gene control [28]. They bind to the 3 untranslated region of target messenger RNAs, leading to translational inhibition or messenger RNA degradation.…”
Section: Nafld Pathogenesismentioning
confidence: 99%
“…Small non-coding RNA molecules called microRNAs (miRNAs) are essential for post-transcriptional gene control [28]. They bind to the 3 untranslated region of target messenger RNAs, leading to translational inhibition or messenger RNA degradation.…”
Section: Nafld Pathogenesismentioning
confidence: 99%
“…Endocrine disorders are the fifth principal cause of mortality worldwide. In recent years, miRNA’s regulatory mechanism could be more effective in diagnostic and therapeutic tools for treating people who have various biological processes associated with endocrine disorders [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…Inversely, low miRNA levels are associated with higher mRNA concentration [ 29 ]. Nearly 60% of the human genome is regulated by miRNAs, suggesting that they are involved in almost all essential cellular functions [ 30 , 31 ]. Mounting evidence has demonstrated that miRNA expression is frequently altered in complex pathophysiologies, including cancer [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%